Compounding stresses confront rural households in southern Malawi - Upton, Joanna; Duchoslav, Jan; Tennant, Elizabeth (International Food Policy Research Institute, 2024)
Southern Malawi has historically been less food secure than the rest of the country, and the current lean season will be no different. The Malawi Vulnerability Assessment Committee expects 2,460,000 people in the Southern Region (29% of its population) to require humanitarian assistance at the peak of the lean season in February and March 2024, compared to 1,560,000 people in the Central Region (18% of its population) and 388,000 people in the Northern Region (15% of its population) (MVAC 2023). The Southern Region is home to 44% of Malawi’s population, but to 56% of those in need of humanitarian assistance. More people in the Southern Region are in danger of going hungry in the coming months than in the Central and Northern regions combined. But who are these people, what is behind their vulnerability, and what does the future have in store for them?